Effect of portable air filtration systems among female residents of old age home in northern India with hazardous air quality - Aman Ahuja; Ashwani Kumar; Rahul Rulia; Rashmi Bhardwaj; Geetika Arya; Vineela Surapaneni; Vishal Raj; Jyothi Geetha Mohankumar; Samruddhi Chougale; Dhruva Chaudhry; Pawan Kumar Singh (Physiological Reports)
Abstract Air pollution is among leading contributors toward cardiovascular diseases. This study evaluated the impact of air filtration systems (AFS) on cardiovascular and oxidative health during severe (hazardous category) pollution season. It was a single‐arm crossover single‐center study conducted at an all‐female old age home. Portable AFS with HEPA (high‐efficiency particulate air) filters were used for 2 weeks during the intervention phase followed by sham AFS for another 2 weeks (single‐blinded). Primary outcome was change in systolic blood pressure (at baseline, after AFS and after sham AFS). Other outcomes include, change in pulse wave velocity, CRP (C‐reactive protein) levels, and 8‐Oxo‐2′‐deoxyguanosine (8‐oxo‐DG). Final analysis included data from 29 subjects with mean age 65.83 ± 6.4 years. At baseline, PM2.5 levels were in hazardous category (PM2.5: 440.38 ± 44.3 μg/m3). With AFS, indoor PM2.5 levels came down (131.0 ± 19.2 μg/m3). After sham AFS, the levels rose back to the baseline (PM2.5: 414.2 ± 32.2 μg/m3). Primary outcome measurement revealed a drop in both systolic (p < 0.001) and diastolic blood pressure (p = 0.14) after installation of AFS. Both CRP and 8‐oxo‐DG followed a similar trend (p < 0.001). Average pulse wave velocity (from 10 subjects) also decreased after AFS but rose back to baseline value after sham AFS (both p < 0.001). Findings of this study showed that AFS though failed to normalize the quality of air but had a positive impact on cardiovascular and inflammatory parameters.